Can personality traits, obesity, depression, anxiety, and quality of life explain the association between migraine and disordered eating attitudes? - HAMAMCI, Mehmet; KARASALAN, Özgül; İNAN, Levent Ertuğrul (Arquivos de Neuro-Psiquiatria, 2020)
Background: Few studies have explored the coexistence of migraine and disordered eating attitudes. Furthermore, the underlying pathophysiological mechanisms of migraine and disordered eating attitude comorbidity are not clearly understood. Objective: This study aimed to investigate the association between migraine and disordered eating attitudes in relation to personality traits, obesity, quality of life, migraine severity, depression, and anxiety. Methods: This study included 91 patients with episodic migraine and 84 healthy control subjects. Self-report questionnaires were used to evaluate anxiety, depression, migraine-related disability, personality traits, quality of life, and eating disorders. Results: The Eating Attitude Test (EAT) showed disordered eating attitudes in 21 patients (23.1%) in the migraine group and eight patients (9.5%) in the control group. Migraine-related disability, anxiety, depression, neuroticism, and quality of life scores were significantly worse in migraine patients with disordered eating attitudes compared to migraine patients without disordered eating attitudes. In migraine patients, eating attitude test scores were positively correlated with migraine-related disability, anxiety, depression, and neuroticism scores, and negatively correlated with quality of life scores. Conclusion: The association of migraine and disordered eating attitudes was shown to be related to depression, anxiety, quality of life and personality traits and may also indicate a more clinically severe migraine. To the best of our knowledge, there is no literature study that deals with all these relevant data together. However, neuropsychiatry-based biological studies are required to better understand this multifaceted association.
Keywords: Headache; Neuroticism; Body Mass Index; Comorbidity; Pain